Physical mapping of the 5S and 18S-25S rRNA genes by FISH as evidence that Arachis duranensis and A. ipaensis are the wild diploid progenitors of A. hypogaea (Leguminosae) - Seijo, José Guillermo (2004)
The 5S and the 18S-25S rRNA genes were physically mapped by fluorescent in situ hybridization (FISH) in all botanical varieties of cultivated peanut Arachis hypogaea (2n = 4x = 40), in the wild tetraploid A. monticola, and in seven wild diploid species considered as putative ancestors of the tetraploids. A detailed karyotype analysis including the FISH signals and the heterochromatic bands was carried out. Molecular cytogenetic landmarks are provided for the construction of a FISH-based karyotype in Arachis species. The size, number, and chromosome position of FISH signals and heterochromatic bands are similar in all A. hypogaea varieties and A. monticola, but vary among the diploid species. Genome constitution of the species is discussed and several chromosome homeologies are established. The bulk of the chromosome markers mapped, together with data on geographical distribution of the taxa, suggest that peanut originated upon domestication of A. monticola and evidence that the diploids A. duranensis and A. ipaensis are the most probable ancestors of both tetraploid species. Allopolyploidy could have arisen by a single event or, if by multiple events, always from the same diploid species.